Penentuan Kapasitas Daya Reaktif Dan Frekuensi Tuning Filter Pasif Untuk Mengurangi Kandungan Arus Harmonik Beban - Prasetijo, Hari (Jenderal Soedirman University, 2008)
This studi involve decresing method of harmonic current content in a radial distribution systems used single tuned passive filter. The distribution systems model consist of transformer 20/0,4 kV supplying groups of non linier loads that is represented by personal computer (PC) and fluorescent lamp 2x40 W as load harmonic current source. Passive filter was installed in PCC bus (0,4 kV) and analysis to be conducted according to IEEE std.1531-2003 and IEEE std. 519-1992. The reesult showed that insalation passive filter in PCC bus will decrease magnitut load harmonic current significantly. The decreasing determined by reactive power capacity and frequency tunning of passive filter.